Induction and general properties of beta-galactosidase and beta-galactoside permease in Pseudomonas BAL-31. - Hidalgo, C. (American Society for Microbiology (ASM), 1977)
The hydrolysis of o-nitrophenyl-beta-D-galactopyranoside (ONPG) by BAL-31, a marine Pseudomonas that acts as a host for bacteriophage PM2, was studied with intact cells and with cell-free extracts. A transport system for ONPG in whole cells and a beta-galactosidase activity in extracts were evident for cells grown on lactose minimal medium. It was found that the addition of isopropylthio-beta-D-galactopyranoside (IPTG) to cells growing in rich medium induced an ONPG hydrolytic activity detectable in cell extracts but cryptic in whole cells. The existence of a transport system for IPTG, which remained cryptic for ONPG, became apparent from studies of the rates of induction of beta-galactosidase as a function of cell mass at different concentrations of IPTG. The main properties of beta-galactosidase and the lactose transport system of BAL-31 were studied in terms of how they were affected by pH, temperature, or by the presence of several sugars. IPTG competitively inhibits the hydrolysis of ONPG by cell extracts. In cells pregrown on lactose, IPTG slightly inhibits the transport of ONPG. Glucose, and with less efficiency lactose, also inhibits the hydrolysis of ONPG in cell extracts. The growth of cells on lactose minimal medium was inhibited by the addition of IPTG. A mechanism for this inhibition and for the inhibition of ONPG transport by IPTG is discussed.